Effect of proteasome inhibitor MG132 on in vitro maturation of pig oocytes - Chmelíková, Eva; Sedmíkova, Markéta; Rajmon, Radko; Petr, Jaroslav; Svestková, Dana; Jílek, Frantisek (Zygote (Cambridge, England), 2004)
The present study aimed to demonstrate the dependence of meiotic maturation in pig oocytes on the activity of the protease complex proteasome. The proteasome inhibitor MG132 blocked the exit of maturing pig oocytes from metaphase I stage. Seventy-five per cent of the oocytes were blocked at metaphase I when they were cultured with 10 microM MG132. The blocking effect of MG132 was expressed only when the oocytes were exposed to an inhibitor before the 18th hour of in vitro culture. The effects of MG132 are fully reversible. However, a significant proportion of oocytes (46%) cultured for 48 h in MG132-supplemented medium and then for 24 h in MG132-free medium did not block meiosis at the stage of metaphase II and underwent spontaneous parthenogenetic activation. On the basis of our data we can conclude that exit from the metaphase I stage of meiosis is proteasome-dependent in pig oocytes matured in vitro. On the other hand, our data also indicate that other proteasome-independent events are involved in regulating the exit from metaphase I.
Keywords: In Vitro Techniques; Animals; Oocytes; Proteasome Inhibitors; techniky in vitro; Cysteine Proteinase Inhibitors; Female; Oogenesis; zvířata; inhibitory cysteinových proteinas; leupeptiny; Leupeptins; oocyty; inhibitory proteasomu; oogeneze; ženské pohlaví; Sus scrofa